2007
DOI: 10.1143/jjap.46.1859
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Control Techniques for TiN Stacked Metal Gate Electrodes for p-Type Metal Insulator Semiconductor Field Effect Transistors

Abstract: A series of new single-step methods and their corresponding algorithms with automatic step size adjustment for model equations of fiber Raman amplifiers are proposed and compared in this paper. On the basis of the Newton-Raphson method, multiple shooting algorithms for the two-point boundary value problems involved in solving Raman amplifier propagation equations are constructed. A verified example shows that, compared with the traditional Runge-Kutta methods, the proposed methods can increase the accuracy by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Figures 4(a The mechanisms of the V fb shift in the TiN gate stacks have been extensively reported. [20][21][22][23] and the Fermi level might be pinned at the midgap of Si. 20) However, in our experiments, Si diffusion was not observed and high-k dielectric was not used.…”
Section: Integrated Bulkmentioning
confidence: 99%
See 1 more Smart Citation
“…Figures 4(a The mechanisms of the V fb shift in the TiN gate stacks have been extensively reported. [20][21][22][23] and the Fermi level might be pinned at the midgap of Si. 20) However, in our experiments, Si diffusion was not observed and high-k dielectric was not used.…”
Section: Integrated Bulkmentioning
confidence: 99%
“…[20][21][22][23] and the Fermi level might be pinned at the midgap of Si. 20) However, in our experiments, Si diffusion was not observed and high-k dielectric was not used. Kadoshima et al reported that very thin TiO x at the TiN/SiO 2 interface was likely formed and modulated the work function.…”
Section: Integrated Bulkmentioning
confidence: 99%
“…The PVD-TiN film could have less impurity, such as carbon and chlorine, and better crystallinity than CVD-TiN. Therefore, the larger crystal of PVD-TiN seemed to block the diffusion of Si and to shift the work function to the positive side (27). Thermal stability of poly-Si/TiN/HfSiON stacks fabricated by PVD-based in-situ method (in-situ PVD-TiN on SPIR-HfSiON) was investigated by using the capacitor fabricated by the flow shown in Fig.…”
Section: Electrical Properties In Poly-si/tin/hfsion Stacked Capacitorsmentioning
confidence: 99%
“…In addition to interfacial SiO 2 growth, it has been reported that metal elements such as Hf and La atoms in high-k layers diffuse into gate electrode after high-temperature activation annealing [1][2][3][4]. Consequently, a loss of leakage reduction merit due to permittivity lowering of Hf-based high-k layer has been pointed out [4].…”
Section: Introductionmentioning
confidence: 99%